German biodiversity assessment goes below ground - Christian Wirth; Helge Bruelheide; Nina Farwig; Jori Marx; Julia S. Ellerbrok; Josef Settele (Soil Organisms)
We are living in times of rapid change and multiple crises. One of the most concerning is the biodiversity crisis. This refers to the global loss of biological diversity caused by us humans: the disappearance of habitats, the rapid change in biotic communities, the shrinking of animal and plant populations, their genetic impoverishment and ultimately their extinction. As a consequence, the functioning and service provisioning of ecosystems also change, often for the worse. These interrelationships were impressively summarised for our planet in the report of the World Biodiversity Council (IPBES 2019). But how does the biodiversity crisis manifest itself in Germany and what are the reasons for these changes? What are the consequences for our ecosystems and thus for our livelihoods? What about our efforts to protect and promote biodiversity? And what are our options to raise awareness and thus to initiate a transformation to an economy with and for biodiversity?